2022
DOI: 10.1186/s12874-022-01747-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and psychometric evaluation of resilience measurement scales for people living with dementia and their carers

Abstract: Psychometrically sound resilience outcome measures are essential to establish how health and care services or interventions can enhance the resilience of people living with dementia (PLWD) and their carers. This paper systematically reviews the literature to identify studies that administered a resilience measurement scale with PLWD and/or their carers and examines the psychometric properties of these measures. Electronic abstract databases and the internet were searched, and an international network contacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…This is an indispensable element in the construction of the care pathway [ 62 , 63 , 64 , 65 ]. Although it would be important to consider other factors regarding the well-being of caregivers such as sense of coherence, burnout, resilience, and coping, we did not include such factors in this study [ 66 , 67 , 68 ]. It is important to investigate this in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This is an indispensable element in the construction of the care pathway [ 62 , 63 , 64 , 65 ]. Although it would be important to consider other factors regarding the well-being of caregivers such as sense of coherence, burnout, resilience, and coping, we did not include such factors in this study [ 66 , 67 , 68 ]. It is important to investigate this in the future.…”
Section: Discussionmentioning
confidence: 99%
“…2 Specifically, Windle et al (2011) identified 19 measures, including 15 original measures and four variations (e.g., CD-RISC-25 vs. CD-RISC-10), and they reported ratings of these measures on their content validity, internal consistency, construct validity, reproducibility/reliability, and interpretability. These criteria offer a useful framework for the current study given its and Terwee et al’s (2007) influence and how they further inform at least two recent systematic reviews on resilience measures ( Zhou et al, 2020 ; Windle et al, 2022 ). 3…”
Section: Literature Reviewmentioning
confidence: 99%
“…(1) content validity, (2) internal consistency, (3) criterion validity, (4) construct validity, (5) reproducibility (including agreement and reliability), (6) responsiveness, (7) floor and ceiling effects, and (8) interpretability. However, several criteria (i.e., gold standard, reproducibility-agreement, floor and ceiling effects, and responsiveness) are typically meaningful in medical/clinical contexts (e.g., clinical trials, interventions, and changes) but are less relevant to the current stage of resilience research (see Windle et al, 2011;Zhou et al, 2020;Windle et al, 2022) and thus were excluded from this review. study given its and Terwee et al 's (2007) influence and how they further inform at least two recent systematic reviews on resilience measures (Zhou et al, 2020;Windle et al, 2022).…”
Section: Existing Systematic Reviews and Current Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…scales and instruments have been used to evaluate individuals' mental health, performance, and personality traits (Linden et al, 2022;Windle et al, 2022). Not only do these evaluations track progress, but they also help tailor interventions to better meet the specific needs of various populations.…”
Section: Co-occurrence Of Abstractmentioning
confidence: 99%